Screening for thalassaemia among group of students of a higher institution – our experience - A.Talib, Norlelawati; Muhammad, Hadijah; Hadzir, Siti Nor Haiza; I, Rusmawati; MS, Salman; Jantan, Abdul Wahab; Muhammad, Siti Aeshah @ Naznin (Faculty of Medicine, International Islamic University Malaysia, 2011)
Introduction: Thalassaemia is an inherited blood disorder and is a significant public health alarm in Malaysia with many not knowing they are carriers of this haemoglobin disorders. Materials and methods: This study conducted a one off collection of blood samples from 72 Malays students of International Islamic University Malaysia (IIUM) in Kuantan. Blood samples were subjected to conventional haemoglobin analyses that include full blood count and picture, HPLC, Haemoglobin electrophoresis and H-inclusion test. All samples were also genotyped for alpha thalassaemia–1 of Southeast Asia (a-Thal1SEA). Result: There were 17(23.6%) students who were diagnosed as thalassaemia carriers. Out of this, four (5.5 %) and six (8.3 %) students were presumptive β-thalassaemia trait and Haemoglobin-E trait as determined by the HPLC assay respectively. Nine (12.5%) students were genotyped a-Thal1SEA among whom two were also β-thalassaemia carriers. All thalassaemia cases had MCH of < 27pg. Nonetheless, two out of six Haemoglobin-E trait and three out of nine a-Thal1SEA carrier had MCV value of >80fL. Two out of four (50%) presumptive β -thalassaemia trait and one out of six (17%) students of presumptive Haemoglobin-E trait had family history of thalassaemia respectively. Conclusion: The high occurrence of the three common types of thalassaemia carrier (β, Hb-E and a-Thal1SEA thalassaemia) in our small group of subjects could be due to better participation of students who had family history of thalassaemia. The study reaffirmed the importance of molecular study for detection of alpha-thalassaemia and the use of MCH value of <27pg rather than MCV value of < 80fL for prediction of thalassaemia. KEYWORDS: Thalassaemia, screening, diagnosis, genetic carriers.